Integrating Gender into a Labor Economics Class - Jacqueline Strenio; Yana van der Meulen Rodgers (Institute of Labor Economics (IZA), 2023)
This article argues that a systematic integration of gender into labor economics courses based on standard textbooks is both beneficial and straightforward. An undergraduate course in labor economics presents an ideal opportunity to introduce students to the importance of gender differences in economic outcomes. We provide a prototype of such a course, and we show how gender-aware content and pedagogical tools can complement a course based on a standard textbook or set of articles. We also review the most popular textbooks in labor economics and show how gender issues are mostly contained in a single chapter on labor market discrimination rather than thoroughly integrated throughout the text. In addition to exposing students to more diverse content and methodologies, mainstreaming gender into an undergraduate labor economics class can help cultivate inclusivity and belongingness in the discipline.
Keywords: A2; J1; O1; 330; labor economics; gender; women; curriculum; COVID-19